THE DEVELOPMENT OF DESIRABLE CHARACTERISTICS OF STUDENT DISCIPLINE BASED ON TRISIKKHA OF PETCHARIK DEMONSTRATION SCHOOL UNDER NAKHON SI THAMMARAT MUNICIPALITY - Padungkit, Nutpaphat; Somkhaoyai , Teeraphong; Klubsri, Suwes (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) to study the current condition of desirable characteristics of student discipline, 2) to study the development of desirable characteristics of student discipline based on Trisikkh principles, 3) to propose guidelines for development of desirable characteristics of student discipline based on Trisikkh principles of Petcharik Demonstration School, under Nakhon Si Thammarat Municipality. This mixed-methods research employed a sample of 60 participants. Data were collected through questionnaires administered to teachers at Petcharik Demonstration School, Nakhon Si Thammarat Municipality and analyzed using mean and standard deviation, as well as content analysis. In-depth interviews were conducted with 10 key informants and 5 experts. Additionally, focus group discussions were held with 7 qualified persons. The qualitative data were analyzed using descriptive analysis. The results of the study found that; 1) The current condition of desirable characteristics of student discipline in quantitative overview, were arranged by descending order with behavior ranked highest, followed by rule compliance and dressing. In qualitative overview found that: in terms of compliance, teachers should record student’s participation in flag-raising activities and promoting activities that did not violate school regulations. In terms of dressing, educated students on proper attire and makeup that did not violate the school regulations. And in terms of behavior, teachers should train students to be mindful and willing to practice correctly using words appropriately and in appropriate places, refraining from using rude words. 2) the development of desirable characteristics of student discipline based on Trisikkh principles, it was found that all 3 aspects, namely, compliance with regulations, dressing and behavior: Controlling students to be in discipline, speech, and mind (Sīla). Organizing activities to train students to use mindfulness and behave according to school rules (Samdhi). Explaining the process of creating discipline according to the intellectual development approach that came from listening, thinking, and acting appropriately to the students' status (Pañña). 3) The proposed approach for development of desirable characteristics of student discipline based on Trisikkh principles of Petcharik Demonstration School under Nakhon Si Thammarat Municipality, was found to be appropriate, feasible, and beneficial in the methods for monitoring and evaluation, including criteria and tools, align with all components of desirable disciplinary characteristics based on Trisikkh principles.